The Effect of Dexamethasone on IL-6 Levels in Confirmed COVID-19 Patients Treated at RSUP Dr. M. Djamil Padang - Bobby Hasibuan; Irvan Medison; Fenty Anggrainy (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Elevated IL-6 levels have been found in COVID-19 patients and are associated with a poor prognosis. According to COVID-19 management guidelines, several types of corticosteroids can be used as therapy modalities for COVID-19 patients, including dexamethasone, methylprednisolone, and hydrocortisone. The purpose of this study was to examine how dexamethasone administration affected changes in IL-6 levels in confirmed COVID-19 patients at RSUP Dr. M. Djamil Padang.Methods: This was a retrospective cohort study with a sample of all COVID-19 patients who met the inclusion and exclusion criteria and were treated in the COVID-19 isolation ward at RSUP Dr. M. Djamil Padang. The study began in June 2021 and concluded in July 2022. The data was analyzed both descriptively and analytically. The distribution of frequencies and proportions of each variable was included in the univariate analysis. Bivariate analysis employs data-scale-appropriate statistical tests such as the T-test to determine the relationship between independent and dependent variables.Results: The characteristic of the patients were mostly 18-49 years old (37.22%), female (55.67%), of severe clinical degree (49.44%), had no comorbidities (52.78%) and the majority (77.78%) received dexamethasone in the recommended dose (1 x 6 mg). The study's findings revealed that there was no difference in IL-6 values before and after dexamethasone administration in patients with moderate clinical degrees, but there were differences in IL-6 values before and after dexamethasone administration in patients with severe and critical clinical degrees.Conclusion: The IL-6 level has significantly decreased following dexamethasone administration. Dexamethasone administration causes significant changes in IL-6 values in severe and critical degrees but not in moderate clinical degree.